Foundations of kinesiology - Oglesby, Carole A.; Henige, Kim; McLaughlin, Douglas W.; Stillwell, Belinda
"Foundations of Kinesiology provides a guided introduction to the discipline and professions of kinesiology using a holistic, learner-centered, and skill-based approach. The text explores the core subdisciplines of kinesiology and allows students to explore the research and physical activity contributions that each has to offer. The text also considers how the discipline is crucial in enabling healthy lives by illustrating real-life scenarios across several chapters"--Provided by publisher.